Experimental investigation on performance characteristics of a small-scale rotating detonation engine - Md Salleh, Mohd Fahmi; Abdul Wahid, Mazlan; Mohd Yusof, Ab Aziz; Mohd Rozaiddin, Umar Ikhwan; Kamaruzaman, Natrah; Sharudin, Hazim; Abu Kasim, Haszeme (UiTM Press, 2026)
A small-scale rotating detonation engine (RDE) is a detonation-based engine with potential propulsion and power generation applications, especially when weight and space are critical factors. In this study, experimental investigations on a small-scale RDE were fueled with a low methane-oxygen mixture flow rate to investigate the performance characteristics, including the detonation wave stability, detonation wave velocity, and thrust generated. The inner and outer annulus diameters of the small-scale RDE are 38 mm and 46 mm, respectively. The total mass flow rate, ṁtotal, of the methane-oxygen mixture employed in the present study was 0.0040 kg/s, and the equivalence ratios, φ, range from 0.8 to 1.2. The result shows two types of instability observed within the tested equivalence range: chaotic instability and waxing and waning instability. The least instability was observed at φ = 1.0, which can be considered the optimal mixture proportion for a stable, small-scale RDE operation. The average detonation wave velocity and thrust were found to increase as the equivalence ratio increased. Meanwhile, the average detonation pressure within the RDE annulus was observed to rise, reaching a maximum value, and decreasing as the equivalence ratio increases. Thus, achieving a well-balanced reactant mixture is important to ensure a stable detonation wave propagation and optimize the overall RDE performance.